1997
DOI: 10.1097/00006123-199708000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral and Ipsilateral Microsurgical Approaches to Carotid-Ophthalmic Aneurysms

Abstract: Giant carotid-ophthalmic aneurysms that are eligible for surgical treatment as well as small and large aneurysms dislocating the optic nerve or the chiasm superomedially or medially should be approached via ipsilateral craniotomies. It is recommended that small and large aneurysms of the carotid-ophthalmic segment originating medially, superomedially, or superiorly, displacing the optic nerve or the chiasm superiorly, superolaterally, or laterally, be approached via contralateral craniotomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 24 publications
1
41
0
5
Order By: Relevance
“…The difficult proximal control and the narrow space to work with lead to a higher frequency of failed clipping procedures as well as to a higher surgical morbidity and mortality [2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…The difficult proximal control and the narrow space to work with lead to a higher frequency of failed clipping procedures as well as to a higher surgical morbidity and mortality [2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…3,5,11,12,21 The contralateral supraorbital keyhole approach has also been described by the pupils of Perneczky in detail. 10,22 Novak et al reported a case of a recurrent posterior fossa craniopharyngioma approached through the cistern magna from the contralateral side with an excellent outcome.…”
Section: Fig 4 Postoperative T2-weighted Axial (A-d) and Contrast-ementioning
confidence: 99%
“…2,4,6,8,17) However, occlusion or stenosis of the ipsilateral ICA sometimes occurs after direct clipping and a high degree of mural sclerosis of the aneurysms and the parent artery is suspected to be one of the most crucial predictors of this phenomenon. 13,14,16,24) In our case, the severe calcification of the aneurysm neck led us to avoid direct clipping.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in skull base surgery have enabled direct clipping of the aneurysm. 2,4,6,8,13,17) The use of endovascular surgery has also increased, but the results of endosaccular coil embolization may be less satisfactory for wide-necked aneurysms or aneurysms causing a mass effect. 3,7,[9][10][11]14,[20][21][22][23] Direct clipping sometimes results in incomplete obliteration of the aneurysm or compromise of the patency of the ICA if severe sclerotic change is present in the wall of the aneurysm neck or the parent artery.…”
Section: Introductionmentioning
confidence: 99%